KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM SEKOLAH TERHADAP KOMITMEN GURU DI SEKOLAH PENGGERAK TINGKAT SMA - Yetti, Yetti; Arafat, Yasir; Mulyadi, Mulyadi (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The purpose of this study was to determine the impact of leadership climate and the atmosphere at the principal's school on the commitment of teachers in one phase and one time. This study uses quantitative methods, the sample of this study is 4 first grade driving schools in the eastern region of Ugan Kumering Ulu with 70 teachers. The author used the method of data collection in this study by conducting direct observations at the research site to understand the work environment, work processes and other relevant methods, and distributing the research questions among all the students of teachers 70. The method of data analysis in this study using normality test, homogeneity test and hypothesis test using anova spps 26. The value of. Sig (2 -tail) is 0.000 mean less than 0.05. and a percentage of 88.3 percent. The Asymp.Sig value (2-tailed) of the school coefficient is 0.006, which is less than 0.05. and a percentage of 38.1 percent. Therefore, it can be said that there is an effect between the school atmosphere and the teacher's commitment to the driving school. The variables of principal management and school climate for teacher loyalty in class 1 run upper secondary school, the Asymp.Sig value (2-tailed) is 0.009, a less than 0.05. and a percentile of 90 percent. So it can be concluded that the accusation is accepted. Therefore, it can be said that the principal's leadership and school climate have an impact on the teacher's involvement in school management.